Histopathologists as lifelong learners - Lokuhetty, M D S (College of Pathologists of Sri Lanka, 2018)
We, practicing histopathologists embark on independent practice with its associated heavy workload following conclusion of our formal professional training and board certification. Over a period of time, it’s natural for us to become comfortable in our diagnostic role and be complacent. Do we voluntarily participate in professional development activities (CPD) to update our knowledge as we move along in our professional carrier? Yes, I think majority of us do participate in CPD activities organized in the local setting. Do we participate in similar activities conducted across borders? Do we take the initiative to explore web based CPD activities to improve our diagnostic skills? We as practicing histopathologists should maintain our competence level at diagnostics by active participation in CPD activities to keep abreast with the rapidly changing domain knowledge. Additionally, do we critically reflect on our diagnostic practice as a self-development activity? Do we know what is meant by critical reflection? Critical reflection includes the ability to rethink, reconsider and reconstruct actions and experiences periodically in a thoughtful and a systemic manner. It is important to critically reflect on four domain areas that are important in our pathology practice to facilitate lifelong learning. These four domain areas are, 1. Correct diagnosis 2. Quality pathology report 3. Acceptable turnaround time 4. Good communication
Keywords: Practicing histopathologists embark; Independent practice